Classical and modern receiver architectures. - Mirabbasi, S. (IEEE Communications magazine)
This article is a review of several classical and modern wireless receiver architectures used in wideband wireless communication systems. The emphasis is on configurations suitable for integration on a single silicon chip. A full understanding of the design trade-offs discussed in this article is necessary for the proper introduction of a new modulation scheme presented in the article by Mirabbasi and Martin (2000) entitled, "Hierarchical QAM: a spectrally efficient DC-free modulation scheme".